Balancing Fluctuating Renewable Energy Generation Using Cogeneration and Heat Pump Systems. Issue 1 (2nd December 2013) - Mueller, Stine; Tuth, Richard; Fischer, David; Wille‐Haussmann, Bernhard; Wittwer, Christof
Abstract Future energy supply will depend increasingly on fluctuating renewable energy generation. This requires new techniques and methods to deal with fluctuations in the grid. Thermal energy systems with thermal storage capacities linked to the electrical grid, for example, combined heat and power (CHP) and heat pump systems can provide additional and necessary storage capacities. This study examines the potential of CHP electricity generation and heat pump electricity consumption in residential buildings to balance fluctuations of renewable energy generation in Germany's future energy system. The optimal operation strategy is derived using mixed integer linear programming. The results show that CHP and heat pump systems can shift electrical energy to balance the residual load. The positive and negative peak load are reduced by 14 % and 33 %, respectively, and the surplus energy generation decreases by 59 %. An increase in thermal storage capacity reinforces these effects.